Management of Ventilator-Associated Pneumonia: Quality Assessment of Clinical Practice Guidelines and Variations in Recommendations on Drug Therapy for Prevention and Treatment - Li, Hong-Yan; Wang, Hai-Shan; Wang, Ying-Lin; Wang, Jing; Huo, Xue-Chen; Zhao, Quan (Frontiers in Pharmacology, 2022)
Purpose: To assess the quality of clinical practice guidelines (CPGs) related to drug therapy for prevention and control of ventilator-associated pneumonia (VAP) and compare the differences and similarities between recommendations. Methods: Electronic databases (including PubMed, Cochrane library, Embase, Web of Science), guideline development organizations, and professional societies were searched to identify CPGs for VAP from January 20, 2012 to January 20, 2022. The Appraisal of Guidelines Research & Evaluation (AGREE) II instrument was used to evaluate the quality of the guidelines. The recommendations on drug therapy for prevention and treatment for each guideline were extracted, and then a descriptive synthesis was performed to analyze the scope/topic, and consistency of the recommendations. Results: Thirteen CPGs were included. The median score and interquartile range (IQR) in each domain are shown below: scope and purpose 72.22% (63.89%,83.33%); stakeholder involvement 44.44% (38.89%,52.78%); rigor of development 43.75% (31.25%,57.29%); clarity and presentation 94.44% (77.78%,94.44%); applicability 20.83 (8.34%,33.34%) and editorial independence 50% (33.33%,66.67%). We extracted 21 recommendations on drug therapy for prevention of VAP and 51 recommendations on drugs used for treatment. Some controversies remained among the included guidelines. Conclusions: There is considerable variability in the development processes and reporting of VAP guidelines. Despite many similarities, the recommendations still had some inconsistencies in the details. For the prevention and treatment of VAP, local microbial epidemiology and antibiotic sensitivity must be considered, and recommendations should be regularly revised as new evidence emerges.